The Value of Ultrasound in Classification of Thyroid Hypoechoic Nodules - Ngoc, Doan Van; Thi Huyen Trang, Hoang; Cong Hoan, Tran; Van Sang, Nguyen; Minh Chau, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2021)
This study evaluates  the value of ultrasound in classifying hypoechoic nodules of thyroid of 70 patients at the Department of Diagnostic Imaging and Oncology of E Hospital from January 2019 to December 2019. The study results show that the patients’ average age was 55.29 ± 13.7; the female/male ratio was approximately 6.5/1; patients with a history of radiotherapy to the neck area and chronic thyroid disease had a very high risk of developing cancer; homogeneous hypoechoic nodules had a higher risk of malignancy than  the heterogeneous; the sign of height ≥ width had the diagnostic value of thyroid malignant nodule with Se = 57.8%, Sp = 89.6%, PPV = 88%, NPV = 89.6%, Acc = 41.4%, OR = 10.03; the sign of border irregularity had the diagnostic value of thyroid malignant nodule with Se = 77.8%, Sp = 80%, PPV = 87.5%, NPV = 66.7%,  Acc = 57.1%, OR = 14; microcalcification has a diagnostic value of thyroid malignant nodule with Se = 71.1%, Sp = 56%, PPV = 17.4%, NPV = 51.9%, Acc = 57.1%, OR = 3.1. TIRADS 4B, 5 actually had a higher risk of malignancy than TIRADS 4A. The study concludes that ultrasound has a great value in orienting malignant lesions of hypoechonic thyroid nodules. Keywords : Thyroid nodule, thyroid hypoechoic nodule, TIRADS. References  [1] F. Bray, J. Ferrlay, I. Soerjomataram et al., Global Cancer statistics 2018: GLOBOCAN Estimates of Incidence and Mortality Worldwide for 36 Cancers in 185 Countries, CA: A Cancer Journal for Clinicians, Vol. 68, No. 6, 2018, pp. 394-424. https://doi.org/full/10.3322/caac.21492. [2] E. Papini, R. Guglielmi, A. Bianchini, A. Crescenzi et al., Risk of Malignancy in Nonpalpable Thyroid Nodules: Predictive Value of Ultrasound and Color-Doppler Features, The Journal of Clinical Endocrinology & Metabolism, Vol. 87, No. 5, 2002, pp. 1941-1946, https://doi.org/10.1210/jcem.87.5.8504. [3] T. T. Hong, Image Characteristics and Value of Ultrasound in the Diagnosis of Localized Thyroid Lesions, Master of Medicine Thesis Majoring in Diagnostic Imaging of Hanoi Medical University, 2013 (in Vietnamese). [4] V. T. Giao, Research on Ultrasound Values in TIRADS Classification of Localized Thyroid Lesions, Master of Medicine Thesis Majoring in Diagnostic Imaging, Hanoi Medical University, 2015 (in Vietnamese). [5] B. Y. Cho, H. S. Choi, Y. J. Park, J. A. Lim, H. Y. Ahn et al., Changes in the Clinicopathological Characteristics and Outcomes of Thyroid Cancer in Korea Over the Past Four Decades, Thyroid, Vol. 23, No. 7, 2013, pp. 797-804, https://doi.org/10.1089/thy.2012.0329. [6] C. M. Oh, S. Park, J. Y. Lee et al., Increased Prevalence of Chronic Lymphocytic Thyroiditis in Korean Patients With Papillary Thyroid Cancer, PLoS One, Vol. 9, No. 6, 2014, pp. 1-7, https://doi.org/10.1371/journal.pone.0099054. [7] G. Grani, L. Lamartina, V. Ramundo, R. Falcone, et al., Taller-Than-Wide Shape: A New Definition Improves the Specificity of TIRADS Systems, Eur Thyroid J, Vol. 9, No. 2, 2020, pp. 85-91, https://doi.org/10.1159/000504219. [8] B. Moifo, E. O. Takoeta, J. Tambe et al., Reliability of Thyroid Imaging Reporting and Data System (TIRADS) Classification in Differentiating Benign from Malignant Thyroid Nodules, Open Journal of Radiology, Vol. 3 No. 3, 2013, pp. 103-107, http://dx.doi.org/10.4236/ojrad.2013.33016. [9] H. J. Moon, J. Y. Kwak, M. J. Kim et al, Can Vascularity at Power Doppler US Help Predict Thyroid Malignancy?, Radiology, Vol. 255, 2010, pp. 260-269, https://doi.org/10.1148/radiol.09091284. [10] E. Horvath, S. Majlis, R. Rossi et al., An Ultrasonogram Reporting System for Thyroid Nodules Stratifying Cancer Risk for Clinical Management, J Clin Endocrinol Metab, Vol. 94 No. 5, 2009, pp. 1748-1751, https://doi.org/10.1210/jc.2008-1724. [11] G. Russ, B. Royer, C. Bigorgne et al., Prospective Evaluation of Thyroid Imaging Reporting and Data System on 4550 Nodules With and Without Elastography, Eur J Endocrinol, Vol. 168, No. 5, 2013, pp. 649-655, https://doi.org/10.1530/EJE-12-0936. [12] J. H. Shin, J. H. Baek, J. Chung et al., Ultrasonography Diagnosis and Imaging-Based Management of Thyroid Nodules: Revised Korean Society of Thyroid Radiology Consensus Statement and Recommendations, Korean J. Radiol., Vol. 17, No. 3, 2016, pp. 370-395, https://dx.doi.org/10.3348%2Fkjr.2016.17.3.370. [13] F. N. Tessler, W. D. Middlenton, E. G. Grant et al., ACR Thyroid Imaging, Reporting and Data System (TI-RADS): White Paper of the ACR TI-RADS Committee, J Am Coll Radiol., Vol. 14, No. 5, 2017, pp. 587-595, https://doi.org/10.1016/j.jacr.2017.01.046. [14] N. T. T. Thao, N. L. Lam, V. D. Luu, Research Into the Value in the Diagnosis of Thyroid Cancer of the EU-TIRADS 2017 Classification, Vietnamese Journal of Radiology, No 33, 2019, pp. 12-18, https://radiology.com.vn/bao-cao-khoa-hoc/nghien-cuu-gia-tri-chan-doan-ung-thu-tuyen-giap-cua-phan-do-eu-tirads-2017-n125.html/, (accessed on: Deceber 4th, 2019) (in Vietnamese).